2004
DOI: 10.1071/ah042710065
|View full text |Cite
|
Sign up to set email alerts
|

Type of housing predicts rate of readmission to hospital but not length of stay in people with schizophrenia on the Gold Coast in Queensland

Abstract: Accommodation is considered to be important by institutions interested in mental health care both in Australia and internationally Some authorities assert that no component of a community mental health system is more important than decent affordable housing. Unfortunately there has been little research in Australia into the consequences of discharging people with a primary diagnosis of schizophrenia to different types of accommodation. This paper uses archival data to investigate the outcomes for people with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 16 publications
(30 reference statements)
2
15
0
Order By: Relevance
“…Another body of evidence demonstrates that if people with schizophrenia have supportive social relationships they have a better quality of life, fewer symptoms, and fewer admissions to hospital. In a related study by the authors of this paper, people with schizophrenia were found to be more likely to be admitted to hospital if they were discharged to a boarding house than if they were discharged to a private home (Browne, Courtney & Meehan, 2004). Their symptoms did not seem to be all that different, nor did their desire for meaningful relationships.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Another body of evidence demonstrates that if people with schizophrenia have supportive social relationships they have a better quality of life, fewer symptoms, and fewer admissions to hospital. In a related study by the authors of this paper, people with schizophrenia were found to be more likely to be admitted to hospital if they were discharged to a boarding house than if they were discharged to a private home (Browne, Courtney & Meehan, 2004). Their symptoms did not seem to be all that different, nor did their desire for meaningful relationships.…”
Section: Discussionmentioning
confidence: 63%
“…Stage 1 used Archival quantitative data to compare length of stay and readmission rates (Browne, Courtney & Meehan 2004) and acute symptoms and global level of functioning in people with schizophrenia living in their own home and for profit boarding houses.…”
Section: Overview Of the Studymentioning
confidence: 99%
“…Post-discharge factors related to the individual vulnerability were reported in 39 papers, among those most frequently studied being compliance to treatment [17, 3037] or to follow-up appointments [31, 33, 36, 3840], the type of housing the patient was discharged to [14, 24, 30, 34, 3945], and the post-discharge alcohol/substance abuse [24, 30, 3436, 40, 46, 47]. The significant results as well as the type of analysis in which these factors were found to be significant (bivariate vs multivariate) as well as the other variables that authors adjusted their results for are included in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Positive outcomes in favor of supported housing include longer housing tenure (4,9,10), better quality of life (11), more meaningful activities and work (12), greater housing satisfaction (13)(14)(15), lower rate of psychiatric hospitalization (16), and lower cost (17,18). Positive outcomes in favor of supported housing include longer housing tenure (4,9,10), better quality of life (11), more meaningful activities and work (12), greater housing satisfaction (13)(14)(15), lower rate of psychiatric hospitalization (16), and lower cost (17,18).…”
mentioning
confidence: 99%